Hesperetin Prevents Bone Resorption by Inhibiting RANKL-Induced Osteoclastogenesis and Jnk Mediated Irf-3/c-Jun Activation - Zhang, Qiang; Tang, Xinqiao; Liu, Zhong; Song, Xiaoxia; Peng, Dan; Zhu, Wei; Ouyang, Zhengxiao; Wang, Wanchun (Frontiers in Pharmacology, 2018)
Bone homeostasis and resorption is regulated by the proper activation of osteoclasts, whose stimulation largely depends on the receptor activator of nuclear factor κB ligand (RANKL)-RANK signaling. Herein, for the first time, we showed that interferon regulatory factor (Irf)-3 was intimately involved in RANKL-induced osteoclast formation. In addition, hesperetin (Hes) derived from citrus fruit could inhibit RANKL-induced osteoclast differentiation and maturation among three types of osteoclast precursors with inhibited formation of F-actin rings and resorption pits on bone slices. More importantly, by using SP600125, a selective Jnk inhibitor, we showed that Hes was able to significantly attenuate the Jnk downstream expression of Irf-3 and c-Jun, thereby inactivating NF-κB/MAPK signaling and transcriptional factor NFATc-1, leading to suppression of osteoclast-specific genes, which resulted in impaired osteoclastogenesis and functionality. An ovariectomized (OVX) osteoporosis mouse model demonstrated that Hes could increase trabecular bone volume fractions (BV/TV), trabecular thickness, and trabecular number, whereas it decreased trabecular separation in OVX mice with well-preserved trabecular bone architecture and decreased levels of TRAP-positive osteoclasts. This is further evidenced by the diminished serum expression of bone resorption marker CTX and enhanced production of osteoblastic ALP in vivo. Taken together, these results suggested that Hes could inhibit Jnk-mediated Irf-3/c-Jun activation, thus attenuating RANKL-induced osteoclast formation and function both in vitro and in vivo.